Effective and Responsive Implementation of German Asylum and Resettlement Procedures for Syrian Refugees from 2015 To 2018 - Abdelmeguid, Nourhan Morsy (AUC Knowledge Fountain, 2022)
The refugee and migrant crises are one of Europe’s most contentious and divisive issues. In particular, Germany is one of the countries most involved in the Syrian refugee crisis. The number of Syrians seeking refuge in Germany is substantial, and it hosts over one million refugees. Germany is also a key participant and stakeholder in the European Union asylum policies. Thus, this thesis examines the responsiveness and effectiveness of asylum proceedings under the crisis-induced from 2015 to 2018. Germany temporarily suspended the Dublin regulation by processing asylum applications despite stopping by other EU countries as a humanitarian response to accommodate Syrian refugees stranded in Hungary. Thus, I examined the effectiveness of the officials’ administrative procedures during the asylum process in terms of subjectivity, inconsistency, and arbitrariness in front-line bureaucrats. On a policy level, the findings illustrated challenges and hurdles in implementing the Dublin agreement and the influence of the right-wing on setting more restrictive policies. In addition, the constant laws changes caused a lack of security for refugees. On an administrative level, the findings presented cases of inconsistent and possible infringement in the asylum procedure between an official in East and West Germany. Moreover, I analyzed the administrative resettlement process as another response while focusing on the effectiveness of the assessment, of actors such as UNHCR and IOM, in terms of design and implementation. As resettlement has no legal basis, it is given as ‘fellowship,’ and host countries have the right to set the criteria they wish. Despite that resettlement is a safe route for migration rather than the life-threatening smuggling road that refugees resort to, the findings presented that resettlement programme criteria set by the host country usually depend on the political wave. This thesis presents a qualitative study using the German experience with the Syrian refugee crisis as a case study using bottom-up interviews, with a total of eleven interviews of Syrians who underwent this process, officials working in the field, an academic researcher, and one non-Syrian refugee who sought asylum in Belgium for comparative procedural analysis. Thus, three primary themes emerged: the macro-view of the EU refugee system, burden-sharing design, and administrative procedures in Germany’s asylum-seeking procedures. Hence, the thesis also recommends a diversity of policy and administrative reforms that aims to improve the effectiveness of asylum and resettlement programmes while at the same time addressing the major procedural barriers that impede refugees’ asylum and protection rights.